Implementasi Pembelajaran Bahasa Arab Pada Program Akselerasi Di MAN 2 Tulungagung - Khoiru Nidak (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
Essentially intellectual level of students very heterogeneous between each other, there are uniquely giftedÂ children who have strong interest in the various areas. Children have talented with such types requireÂ specific educational services in order to grow their potential so it can actualize themselves optimally. WithoutÂ relevant education services, gifted children will be the group â€œwrong parenting childrenâ€ who failed to provideÂ a significant contribution to the progress of the nation. One form of educational services for students whoÂ have exceptional ability and intelligence is through the Acceleration Program (accelerated learning), kind ofÂ a program to accelerate the period of study for students who have high intelligence and are entitled to receiveÂ special attention in order to stimulate the development of achievements and talents. Therefore, in the learningÂ process in madrasah is needed a proper implementation of the curriculum and can facilitate their potential,Â especially associated with the Arabic language curriculum as a pillar for education based on Islam.Â In accordance with the identification of problems arising at the location, this research is limited to theÂ implementation of Arabic language learning in which related with the method and the strategy chosen by theÂ teacher for teaching, the media and the tools needed and applied curriculum, so this study focused on identifyingÂ implementation learning Arabic and the problems faced by teachers in teaching Arabic at accelerated classesÂ in MAN 2 Tulungagung.Â As defined formula, this research was designed using qualitative descriptive approach. This approach wasÂ chosen because research will produce descriptive data and then analyzed and interpreted to get a conclusion.